Ciliary neurotrophic factor enhances neuronal survival in embryonic rat hippocampal cultures - Ip, NY (J Neurosci, 1991)
First described as a survival factor for chick ciliary ganglion neurons, ciliary neurotrophic factor (CNTF) has recently been shown to promote survival of chick embryo motor neurons. We now report neurotrophic effects of CNTF toward three populations of rat hippocampal neurons, the first demonstration of effects of CNTF upon rodent CNS neurons in culture. CNTF elicited an increase in the neurofilament content of hippocampal cultures prepared from embryonic day 18 (E18) rat brain. This was accompanied by increases of 2-, 28-, and 3-fold in the number of GABAergic, cholinergic, and calbindin- immunopositive cells, respectively. CNTF totally prevented the 67% loss of GABAergic neurons that occurred in control cultures over 8 d. CNTF also increased high-affinity GABA uptake and glutamic acid decarboxylase activity. Effects of CNTF were in all cases dose dependent, with maximal stimulation at approximately 100 pg/ml. When addition was delayed for 3 d, CNTF failed to elicit increases either in the number of cholinergic neurons or in GABA uptake.